Ultrafast Charge‐Transfer Reactions of Indoline Dyes with Anchoring Alkyl Chains of Varying Length in Mesoporous ZnO Solar Cells. Issue 5 (24th March 2015) - Rohwer, Egmont; Minda, Iulia; Tauscher, Gabriele; Richter, Christoph; Miura, Hidetoshi; Schlettwein, Derck; Schwoerer, Heinrich
Abstract: The front cover artwork is provided by H. Schwoerer and I. Minda (Stellenbosch University). The image shows one of our cells in the African sun light with an indoline dye attached and accompanied by a femtosecond transient absorption landscape. Read the full text of the article at 10.1002/cphc.201402784 . Abstract : "The motivation behind these studies is to systematically access new donator–acceptor combinations to optimize the conversion of light energy into electrical energy…︁‥" This and more about the story behind the front cover research can be found at10.1002/cphc.201402784 .